Review of the implementation of the recommendations of the Commonwealth Secretariat/World Bank Joint Task Force report : small states : meeting the challenges in the global economy (Commonwealth Secretariat LondonGB, 2003)
Reviews the progress that the Commonwealth Secretariat has made in implementing the recommendations of the Commonwealth Secretariat/World Bank Joint Task Force Report on Small States. Reports on the progress made by the partner organisations which participated in the preparation of the report and in implementing the actions contained in their frameworks.
Keywords: SMALL STATES